Efeitos do espaço de alojamento e da idade sobre desenvolvimento, integridade e proteção da mucosa intestinal de frangos de corte - Thimotheo, M. [UNESP]; Alves, M.F.R. [UNESP]; Abe, F.R. [UNESP]; Boleli, Isabel Cristina [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
Foi avaliado se o espaço de alojamento influencia o desenvolvimento da mucosa do intestino delgado de frangos, sendo usado um esquema fatorial 4 x 2 (14, 28, 42, 55 dias de idade e alojamento pequeno: 0,11m²/ave e grande: 0,525m²/ave). Foram analisadas: altura, perímetro e número dos vilos, profundidade das criptas, número de células caliciformes e número de vilos sem e com perda de epitélio e exposição do conjuntivo. em ambos os espaços de alojamento, o número de vilos diminuiu e a profundidade das criptas aumentou com a idade nas três regiões intestinais. A altura e o perímetro dos vilos aumentaram de 14 para 28 dias no jejuno e íleo, e o número de células caliciformes foi maior no duodeno e íleo a partir dos 42 dias. A perda de epitélio pelos vilos do íleo aumentou com a idade. Nas aves do alojamento grande, ocorreu aumento na altura e no perímetro dos vilos duodenais com a idade, possibilitado pelo aumento na profundidade das criptas, que resultou em vilos maiores nessas aves do que nas do alojamento pequeno aos 55 dias de idade. O número de células caliciformes diminuiu nas aves do alojamento pequeno aos 42 dias de idade. Os dados mostram que o tamanho do alojamento interferiu no modelo de desenvolvimento temporal da mucosa intestinal e que frangos apresentaram maior tamanho de vilo duodenal quando alojados em espaço maior.

This study evaluated if enclosure size and age influence the intestinal mucosa development of broiler chickens, using an experimental design in an 4x2 factorial arrangement (14, 18, 42 and 55 days of age and two enclosure spaces: small= 0.11m² /bird and large= 0.525m²/bird). Villous height, perimeter and number, and crypt depth, goblet cells number, and number of villous without and with epithelium loss and conjunctive tissue exposition were analyzed in duodenum, jejunum and ileum. Regardless of enclosure size, the villous number diminished and the crypt depth increased with the age in the three intestinal regions. From 14 to 28 days of age, villous height and perimeter increased in the jejunum and ileum. The number of goblet cells was greater from 42 days in duodenum and ileum, and epithelium loss increased until 42 days in the ileum. Broilers housed in small and large enclosures differed in the intestinal characteristics from 42 days. In broilers housed in large enclosure, duodenal villous height and perimeter increased with the age, with an increase in the crypt depth, reaching greater size at 55 days of age than duodenal villous of the broilers housed in a small enclosure. These later presented at 42 days a smaller number of goblet cells than the former. According these results, enclosure size influenced the temporal pattern of the intestinal mucosa development, and broilers presented major duodenal villous growth when housed in large enclosures.
Effects of enclosure size and age on development, integrity and protection of the intestinal mucosa in broiler chickens
Keywords: Broiler chicken; goblet cell; epithelium loss; Intestine; space of housing; villus; célula caliciforme; espaço de alojamento; Frango de corte; intestino; perda de epitélio; vilos